The Johannesburg Convention on Mutual Customs Assistance - is a new tool failing earliy? - Carsten Weerth (Customs Scientific Journal CUSTOMS, 2016)
The Johannesburg Convention on Mutual Administrative Assistance in Customs Matters as of 2003 is a crucial breakthrough and important legal tool for the implementation of risk analysis systems by customs authorities governed by the the World Customs Organization (WCO) around the globe. However it has not entered into force yet. Is this new legal tool failing early? The old Nairobi Convention from 1977 is outdated and has never been widely accepted. This paper addresses the need for mutual Customs assistance, a common legal basis and analyses the current situation. The author underlines the idea that the Johannesburg Convention recognises the increased global concern for the security and facilitation of the international trade supply chain, and that offences against customs law are prejudicial to the security of the Contracting Parties and their economic, commercial, fiscal, social, public health and cultural interests. It also recognises that the international exchange of information is an essential component of effective risk management and that such exchange of information should be based on clear legal provisions. The author also points out that though mutual customs ssistance is possible on the basis of the Nairobi Convention or on the basis of bilateral agreements and other binding or non-binding WCO and/or UN legal tools, the Johannesburg Convention would make things better, clearer and modern. In conclusion the author argues that in case the JC is not going to be ratified by most countries the overall aim of a more secure supply chain is about to fail due to administrational hindering and hesitating governments. The methods used during the study are analysis, synthesis, comparison, generalization, systematic and functional analysis.
Additional information: Also available in Russian
Keywords: F15; F53; K42; 330; Customs Law; International Law; World Customs Organization; Cooperation